PENERAPAN TEKNOLOGI FOOD DEHYDRATOR PADA PENGOLAHAN TANAMAN HORTIKULTURA DI KWT BANGUN MAKMUR DESA KARANGSARI - Dian, Anisha; Hakim, Hakim; Amriyati Azzizzah, Frida (LPPM Universitas Bina Bangsa, 2025)
The Women Farmer’s Group is a community organization whose activities focus on agriculture with an orientation towards developing the village economy. The Bangun Makmur Women's Farmers Group has the problem of not having the knowledge and abilities (skills) for post-harvest processing innovation, appropriate technology and facilities that support marketing. Service methods include identification, program outreach, post-harvest processing training and use of appropriate technology. The results of the PKM program include the implementation of program outreach, the application of food dehydrator technology, the practice of making healthy noodles from vegetable powder coloring as well as assistance with product packaging and photos to support product marketing. The existence of PKM activities has a positive impact on members in the form of knowledge and skills by 75%.